Ekonomi Islam di Era Digital: Peluang dan Tantangan dalam Dunia Bisnis Modern - Zakaria, Andi; Haironi, Rita; Varadila, Usvim (Universitas Batanghari Jambi, 2025)
This study aims to analyze the opportunities and challenges of Islamic economics in the digital era, as well as provide strategic solutions that can be applied to encourage the growth of this sector. This study uses a qualitative method with a descriptive-analytical approach. Data were obtained through literature studies from various articles, industry reports, and recent publications, which were then analyzed to identify patterns, trends, and key challenges faced by sharia business actors in the digital world. The focus of this study includes the sharia fintech sector, halal e-commerce, and the adoption of digital technology in sharia-based businesses. The results of the study show that the Islamic economy in the digital era has great potential to develop globally, especially in countries with high Muslim populations such as Indonesia and Malaysia. The growth of sharia fintech has reached significant numbers, while halal e-commerce continues to expand its global market share. The main challenges identified include the lack of uniform regulations at the international level, low digital literacy among sharia business actors, and the need for stricter supervision of halal products on digital platforms.